What Might I Like My Kids to Learn about Life?: In Search of “Tradition” - Anthony McCann (Journal of Ethnology and Folkloristics)
This personal exploration of “tradition” started after my father died, an event which sparked a series of inner conversations about being a son, being a parent, and the learning that happens over generations. What do I mean by “tradition”? What kinds of conversations would I like the term to open up for me? If I were to consider it as a signpost, what conversations, communities, and contexts might it point to? I work to clarify what “tradition” can mean for me, outlining a wish-list of the aspects I would like my own understanding of “tradition” to encompass. I highlight two common approaches to “tradition” I would like to steer away from: “tradition” as prescriptive-invariance, and “tradition” as resource management. I offer a personal-is-political account of “tradition” to open up analytic opportunities, as I seek to make more appropriate sense of learnings, relationships, and death.